2013
DOI: 10.1164/rccm.201204-0750oc
|View full text |Cite
|
Sign up to set email alerts
|

P2X7-Regulated Protection from Exacerbations and Loss of Control Is Independent of Asthma Maintenance Therapy

Abstract: Rationale: The function of the P2X 7 nucleotide receptor protects against exacerbation in people with mild-intermittent asthma during viral illnesses, but the impact of disease severity and maintenance therapy has not been studied. Objectives: To evaluate the association between P2X 7 , asthma exacerbations, and incomplete symptom control in a more diverse population. Methods: A matched P2RX7 genetic case-control was performed with samples from Asthma Clinical Research Network trial participants enrolled befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…Indeed, several previous studies indicated that P2X7 is implicated in the pathogenesis of airway allergic inflammation in mice and humans (Denlinger et al, 2013;Idzko et al, 2007;Manthei et al, 2012;Mü ller et al, 2011) as well as contact hypersensitivity in a mouse model (Weber et al, 2010). However, all of these studies focused on dendritic cells as a target of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several previous studies indicated that P2X7 is implicated in the pathogenesis of airway allergic inflammation in mice and humans (Denlinger et al, 2013;Idzko et al, 2007;Manthei et al, 2012;Mü ller et al, 2011) as well as contact hypersensitivity in a mouse model (Weber et al, 2010). However, all of these studies focused on dendritic cells as a target of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, blood neutrophils harvested from the patients with COPD show a stronger chemotaxis and an elastase release in response to ATP treatment compared with the control subjects (92). In patients with asthma, in addition to increased levels of ATP in BALF, the functional activity or Single Nucleotide Polymorphism of P2X7R is also associated with the exacerbation or severity of asthma (33,96). While the pathogenesis of these lung diseases differs from each other, inflammatory responses are commonly involved in the development and acute exacerbation of these diseases.…”
Section: Plasmamentioning
confidence: 99%
“…Attenuated whole blood monocyte P2X 7 pore activity in mild-intermittent asthmatics is associated with 11 times odds of developing an asthma exacerbation and 15 times odds of developing an asthma exacerbation in the presence of rhinovirus and use of ICS[61]. In a case-control study, the rs2230911:C>G SNP in P2RX7 was significantly associated with a history of prednisone use in African American asthmatics adjusted for ICS and long-acting beta-agonist use[62]. In a multi-ethnic population of moderate severe asthmatics, individuals with attenuated P2X 7 pore function were found to have a higher rate of asthma exacerbations despite medium-dose ICS use[62].…”
Section: 0 Asthma Exacerbation Genes Identified By Candidate Gene Smentioning
confidence: 99%
“…In a case-control study, the rs2230911:C>G SNP in P2RX7 was significantly associated with a history of prednisone use in African American asthmatics adjusted for ICS and long-acting beta-agonist use[62]. In a multi-ethnic population of moderate severe asthmatics, individuals with attenuated P2X 7 pore function were found to have a higher rate of asthma exacerbations despite medium-dose ICS use[62]. …”
Section: 0 Asthma Exacerbation Genes Identified By Candidate Gene Smentioning
confidence: 99%